Comparison of two immunotoxins against DLL3 receptor; as an inhibitor for small cell lung cancer - Ataee, Mohammad Hossein; Mirhosseini, Seyed Ali; Mirnejad, Reza; Hosseini, Hamideh Mahmoodzadeh; Amani, Jafar (Frontiers in Molecular Biosciences, 2025)
Despite the efforts of researchers to develop new treatments for small cell lung cancer (SCLC), achieving effective treatment has not yet happened. Targeted therapy utilizing delta-like ligand 3 (DLL3), which is highly expressed in SCLC patients, holds promise as a potential solution. Immunotoxins, consisting of bacterial toxins from the ADP-ribosyl transferase toxin family have shown effectiveness in targeting cancer cells. In this study, we investigated the binding ability, cytotoxicity, apoptosis induction rate, and permeability of two immunotoxins based on the rovalpituzumab antibody. The binding ability of immunotoxins to the receptor was performed by the Cell-ELISA method. Following this, the cell viability of cancer and normal cells immunotoxins was evaluated using the MTT assay. The ability to induce apoptosis and the penetration of immunotoxins was assessed by flow cytometry and Western blotting method. The binding ability of the immunotoxin Rova-Typh to the DLL3 receptor was higher compared to the immunotoxin Rova-GrB. The cell viability of A549 cancer cells treated with immunotoxins showed IC50 concentrations of 338 and 734 nM for immunotoxins Rova-GrB and Rova-Typh, respectively. The induction of apoptosis by immunotoxin Rova-Typh was greater compared to immunotoxin Rova-GrB. The designed immunotoxins in prokaryotic hosts exhibit good anticancer performance in A549 lung cancer cells. Additionally, the bacterial toxin-based immunotoxin has a greater ability to induce apoptosis compared to human enzymes and can be considered as a therapeutic option for SCLC cancer.